The role of physical therapists in the context of family health support centers - Cássia Cristina Braghini; Fátima Ferretti; Lucimare Ferraz
Abstract Introduction: Since 2008, with the establishment of Family Health Support Centers (NASF), physiotherapists have been listed among professionals to be included in the team. Physical therapists have many assignments in the NASF, which are conducted through group sessions, in the households, with complementary and integrative practices, lectures and referrals to reference services. Objective: To analyze role and obstacles to the realization of the work of the physiotherapists in NASF. Methods: This is a qualitative research, guided by the case study method. The population was composed by eight physiotherapists active in NASF. Participant observation and semi-structured interviews with physiotherapists were used for data collection. Results: The actions performed by physiotherapists consist of group assistance, home visits, ear therapy and oxygen therapy and activities of health education and disease prevention. As for the barriers, these included lack of training to work at NASF; structural and organizational impediments; insufficient workload and fragility of professional training to work with public health. Conclusion: The role of physiotherapists is in line, in part, with the guidelines recommended by NASF, but principles as matrix support and collective pacts need to be strengthened.